2020
DOI: 10.21041/ra.v10i2.477
|View full text |Cite
|
Sign up to set email alerts
|

Use of supplementary cementitious materials (SCMs) in reinforced concrete systems – Benefits and limitations

Abstract: About a decade of research carried out at IIT Madras on cementitious systems has shown that the partial replacement of portland cement with supplementary cementitious materials (SCMs) has benefits as well as limitations. The SCMs do not adversely affect the long-term compressive strength and drying shrinkage of concretes, though there may be some compromise in workability and the resistance against plastic shrinkage cracking. Through the assessment of the chloride ingress rate in concrete and chloride threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…On the other hand, SCM-based concretes have a lower CH content and, hence exhibits a lower carbonation tolerance because of the prolonged pozzolanic reactions. Due to the lower amount of CH in SCM-based systems, CO 2 is able to carbonate the C-S-H faster, and hence accelerates the carbonation process (Pillai et al 2020). Singh et al (Singh et al 2019) observed that concrete containing 40 wt.…”
Section: Estimation Of Alkalinity and Free Chloride Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, SCM-based concretes have a lower CH content and, hence exhibits a lower carbonation tolerance because of the prolonged pozzolanic reactions. Due to the lower amount of CH in SCM-based systems, CO 2 is able to carbonate the C-S-H faster, and hence accelerates the carbonation process (Pillai et al 2020). Singh et al (Singh et al 2019) observed that concrete containing 40 wt.…”
Section: Estimation Of Alkalinity and Free Chloride Contentsmentioning
confidence: 99%
“…1988). A study by Pillai et al (Pillai et al 2020) shows that even though concrete blended with SCMs shows a higher carbonation, it may not directly contribute to reinforcement corrosion. The propagation of corrosion, however, will still rely on the availability of moisture and oxygen, as well as the resistivity of the medium.…”
Section: Estimation Of Alkalinity and Free Chloride Contentsmentioning
confidence: 99%
“…However, the ingression of these aggressive fluids into the concrete can be delayed by using denser concrete [12]. Incorporating binder components of lower particle size and higher fineness is necessary to decrease the concrete's permeability [13,14]. Therefore, utilizing SCMs like FA, GGBS, metakaolin, rice husk ash, etc, which possess these properties, will potentially replace cement in concrete, enhancing both durability and sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reduction in the use of PC is one of the ways to reduce CO2 emissions by the building materials sector. In the past several decades, the partial replacement of PC with supplementary cementitious materials (SCMs) has gained wide acceptance to increase the quality of concrete and reduce CO2 emissions [4]. In the Netherlands, up to 85% of slag was used to replace PC in one of the projects during 90's.…”
Section: Introductionmentioning
confidence: 99%